2009
DOI: 10.1021/jp909412h
|View full text |Cite
|
Sign up to set email alerts
|

Platinum−Bismuth-Catalyzed Oxidation of Glycerol: Kinetics and the Origin of Selective Deactivation

Abstract: The selective oxidation of glycerol to dihydroxyacetone is still a challenging task for heterogeneous catalysis and important to the chemical industry. Especially bimetallic Pt-Bi catalysts show a high initial selectivity to dihydroxyacetone in acidic media but exhibit a strong deactivation during reaction as well. This deactivation decreases activity as well as selectivity to dihydroxyacetone. Thus, only moderate yields may be achieved. In this work, product adsorption was identified as a major cause. In part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
89
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(98 citation statements)
references
References 21 publications
(46 reference statements)
6
89
0
3
Order By: Relevance
“…The experimentally obtained E A in this work, as shown in Table 1, is in good agreement with the 38 kJ mol À1 value reported by Wörz et al [27] for glycerol oxidation, although their work was based on a Pt-Bi/C catalyst. Demirel et al [28] also reported activation energies of between 40 and 50 kJ mol…”
Section: Advanced Chemical Kinetics 120supporting
confidence: 91%
“…The experimentally obtained E A in this work, as shown in Table 1, is in good agreement with the 38 kJ mol À1 value reported by Wörz et al [27] for glycerol oxidation, although their work was based on a Pt-Bi/C catalyst. Demirel et al [28] also reported activation energies of between 40 and 50 kJ mol…”
Section: Advanced Chemical Kinetics 120supporting
confidence: 91%
“…Based on the experimental evidence obtained with Pt(3.0 wt.%)/C and Pd(4.0 wt.%)-Pt(1.0 wt.%)-Bi(5.0 wt.%)/C catalysts, and the indications made by Worz et al (2009), a reaction network was assumed (Scheme 1). According to the proposal, the oxidation of the primary OH group of glycerol (GLY) leads mainly to glyceric acid (GLYA), followed by tartronic acid (TTA).…”
Section: Kinetic Modelingmentioning
confidence: 99%
“…Scheme 1: Reaction network of the glycerol oxidation (Worz et al, 2009 Scheme 2: Simplified reaction network for the catalytic oxidation of glycerol in alkaline medium. …”
Section: Kinetic Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…4,[128][129][130][131][132] Some promising derivatives include dihydroxyacetone (DHA), glyceric acid (GLS) and H 2 . Fig.…”
Section: Glycerol Reformingmentioning
confidence: 99%